Famílias de usuários de bebida alcoólica: aspectos estruturais e funcionais fundamentados no Modelo Calgary* - Beatriz Ferreira Martins Tucci; Magda Lúcia Félix de Oliveira (Universidade Federal do Ceará, 2019)
Objective to describe the structural and functional aspects and support networks of families living with users of alcoholic beverages.Methods a cross-sectional descriptive study, methodological reference of the Calgary Family Assessment Model, based on semi-structured interviews with the genogram and eco-map tools, carried out with relatives of four construction workers hospitalized for injuries related to alcoholic beverage use, and notified to an information and toxicological assistance center.Results there was a reduction of the children between the generations, but the use of drugs was expanding in the families. Distant and conflicted family relationships were found. The neighborhood support network was strongly linked, but the support of Primary Health Care was a weak link.Conclusion the structural and functional evaluation of the families propitiated knowledge for health promotion, treatment and recovery processes to restore fragile family relationships.